Time course of right‐hemisphere recruitment during word production following left‐hemisphere damage: A single case of young stroke. (11th September 2022) - Chupina, Irina; Sierpowska, Joanna; Zheng, Xiaochen Y.; Dewenter, Anna; Piastra, Maria‐Carla; Piai, Vitória
Abstract: Our understanding of post‐stroke language function is largely based on older age groups, who show increasing age‐related brain pathology and neural reorganisation. To illustrate language outcomes in the young‐adult brain, we present the case of J., a 23‐year‐old woman with chronic aphasia from a left‐hemisphere stroke affecting the temporal lobe. Diffusion MRI‐based tractography indicated that J.'s language‐relevant white‐matter structures were severely damaged. Employing magnetoencephalography (MEG), we explored J.'s conceptual preparation and word planning abilities using context‐driven and bare picture‐naming tasks. These revealed naming deficits, manifesting as word‐finding difficulties and semantic paraphasias about half of the time. Naming was however facilitated by semantically constraining lead‐in sentences. Altogether, this pattern indicates disrupted lexical‐semantic and phonological retrieval abilities. MEG revealed that J.'s conceptual and naming‐related neural responses were supported by the right hemisphere, compared to the typical left‐lateralised brain response of a matched control. Differential recruitment of right‐hemisphere structures (330–440 ms post‐picture onset) was found concurrently during successful naming (right mid‐to‐posterior temporal lobe) and word‐finding attempts (right inferior frontal gyrus). Disconnection of the temporal lobes via corpus callosum was not critical for recruitment of the right hemisphere in visually guided naming, possibly due to neural activity right lateralising from the outset. Although J.'s right hemisphere responded in a timely manner during word planning, its lexical and phonological retrieval abilities remained modest. Abstract : Using two tasks, we investigated word production abilities of J., a 23‐year‐old woman with chronic aphasia from a left‐hemisphere stroke. Magnetoencephalography revealed that, compared to the typical left‐lateralised brain response, J.'s neural responses originated in the right hemisphere. Importantly, right‐hemisphere structures were recruited concurrently (330–440 ms post‐picture onset) but spatially differentially during successful naming (right mid‐to‐posterior temporal lobe) and word‐finding attempts (right inferior frontal gyrus).